The Effect of Stiff Foot Plate Length on Walking Gait Mechanics - Schmitthenner, Dave; Sweeny, Carolyn; Du, Jing; Martin, Anne E (Journal of biomechanical engineering, 2020)
Exoskeletons are increasingly being used to treat gait pathologies. Many of these exoskeletons use a foot plate to actuate the foot, altering the effective stiffness of the foot. Stiffness of the biological foot and ankle plays an important role in the energy modulating function of the leg, so it is important to examine how a foot plate in and of itself impacts gait. Therefore, this study quantified how foot plates themselves alter the walking gait of 16 healthy young adults. The effect of the foot plate length was also examined through the use of two foot plates, one that ended at the metatarsals and one that extended past the toes, about 20% longer. Gait parameters examined included walking speed, step frequency, joint angles for the hip, knee, ankle, forefoot, and toe, ground reaction forces (GRF), and foot-ankle power. The most significant changes were caused by the full plate, which caused an average 13% decrease in the ankle range of motion (ROM) and a 23% decrease in forward GRF at push off. The shorter plate also decreased ankle ROM to a lesser degree. This indicates that the presence of a foot plate impacted foot and ankle kinematics. However, the presence of the tested foot plate had no effect on walking speed or hip or knee kinematics. This indicates that subjects were mostly able to compensate both kinematically and energetically via their foot and ankle for the increased foot stiffness due to the tested foot plate.